Drought-induced photosynthetic inhibition and autumn recovery in two Mediterranean oak species (Quercus ilex and Quercus suber) - Vaz, M; Pereira, J S; Gazarini, L C; David, T S; David, J S; Rodrigues, A; MAROCO, J; Chaves, M M (Tree Physiology, 2010)
Responses of leaf water relations and photosynthesis to summer drought and autumn rewetting were studied in two evergreen Mediterranean oak species, Quercus ilex spp. rotundifolia and Quercus suber. The predawn leaf water potential (ΨlPD), stomatal conductance (gs) and photosynthetic rate (A) at ambient conditions were measured seasonally over a 3-year period. We also measured the photosynthetic response to light and to intercellular CO2 (A/PPFD and A/Ci response curves) under water stress (summer) and after recovery due to autumn rainfall. Photosynthetic parameters, Vcmax, Jmax and triose phosphate utilization (TPU) rate, were estimated using the Farquhar model. RuBisCo activity, leaf chlorophyll, leaf nitrogen concentration and leaf carbohydrate concentration were also measured. All measurements were performed in the spring leaves of the current year. In both species, the predawn leaf water potential, stomatal conductance and photosynthetic rate peaked in spring, progressively declined throughout the summer and recovered upon autumn rainfall. During the drought period, Q. ilex maintained a higher predawn leaf water potential and stomatal conductance than Q. suber. During this period, we found that photosynthesis was not only limited by stomatal closure, but was also downregulated as a consequence of a decrease in the maximum carboxylation rate (Vcmax) and the light-saturated rate of photosynthetic electron transport (Jmax) in both species. The Vcmax and Jmax increased after the first autumnal rains and this increase was related to RuBisCo activity, leaf nitrogen concentration and chlorophyll concentration. In addition, an increase in the TPU rate and in soluble leaf sugar concentration was observed in this period. The results obtained indicate a high resilience of the photosynthetic apparatus to summer drought as well as good recovery in the following autumn rains of these evergreen oak species.
10.1093/treephys/tpq044
Keywords: biochemical parameters; Drought; Mediterranean; photosynthesis; Quercus ilex; Quercus suber; Recovery; water relations

Seasonal physiological responses of Argania spinosa tree from Mediterranean to semi-arid climate - Díaz-Barradas, Mari Cruz; Zunzunegui, María; Ain-Lhout, Fatima; Jáuregui, Juan; Boutaleb, Said; Álvarez-Cansino, Leonor; Esquivias, Mari Paz (Plant and Soil, 2010)
Argania spinosa (the argan tree) is a slowgrowing tree endemic of Morocco, growing on semiarid areas where no other tree species can live. With the aim of predicting temporal changes in A. spinosa woodlands under a probable increase in aridity, we set off to investigate these questions: how do A. spinosa physiological attributes respond to variations in climatic conditions and seasonality, and which is the set of attributes that most affects tree response to environmental conditions? In three study sites, Beni Snassen (North), High-Atlas (Mountain) and Admine Forest in Agadir (Coastal), gas exchange measurements, photochemical efficiency, leaf water potential and different leaf attributes were monitored in February, July and November of 2006. The Mountain site presents the most continental climate. Trees in this site were the most stressed in summer, having the lowest midday leaf water potential values, photochemical efficiency and assimilation rates. We found a Ψmd threshold around -4 MPa, below which stomatal conductance responds linearly to Ψmd . Plants from the North area never reached this threshold during the study period. Although leaf pigments presented a clear seasonal pattern, leaves from Coastal trees exhibit the highest content for each season. The three study sites were separated by two discriminate functions obtained by canonical discriminant analysis. In summer, the Mountain population is separated from the other sites mainly by assimilation rate and Fv /Fm, while in winter transpiration rates and chlorophyll content are the main discriminant variables. Our study shows that A. spinosa trees adjust their physiological status and leaf attributes to environmental conditions allowing plants to thrive under a dry climate. Under a scenario of global change, the distribution of the argan tree likely shifts to milder areas.
Keywords: Browsing; Drought; leaf traits; photochemical efficiency; Stomatal conductance; water relations

Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity - Gullo, M A Lo; Salleo, S; Rosso, R; Trifilo, P (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.
Keywords: cavitation; Drought resistance; hydraulics; Mediterranean trees; Reforestation; water relations

Transpiration and stomatal behaviour of Quercus ilex plants during the summer in a Mediterranean carbon dioxide spring - Tognetti, R; Longobucco, A; Miglietta, F; Raschi, A (Plant, Cell & Environment, 1998)
Variations in the water relations and stomatal response of Quercus ilex were analysed under field conditions by comparing trees at two locations in a Mediterranean environment during two consecutive summers (1993 and 1994). We used the heat-pulse velocity technique to estimate transpirational water use of trees during a 5 month period from June to November 1994. At the end of sap flow measurements, the trees were harvested, and the foliage and sapwood area measured. A distinct environmental gradient exists between the two sites with higher atmospheric CO2 concentrations in the proximity of a natural CO2 spring. Trees at the spring site have been growing for generations in elevated atmospheric CO2 concentrations. At both sites, maximum leaf conductance was related to predawn shoot water potential. The effects of water deficits on water relations and whole-plant transpiration during the summer drought were severe. Leaf conductance and water potential recovered after major rainfall in September to predrought values. Sap flow, leaf conductance and predawn water potential decreased in parallel with increases in hydraulic resistance, reaching a minimum in mid-summer. These relationships are in agreement with the hypothesis of the stomatal control of transpiration to prevent desiccation damage but also to avoid ‘runaway embolism’. Trees at the CO2 spring underwent less reduction in hydraulic resistance for a given value of predawn water potential. The decrease in leaf conductance caused by elevated CO2 was limited and tended to be less at high than at low atmospheric vapour pressure deficit. Mean (and diurnal) sap flux were consistently higher in the control site trees than in the CO2 spring trees. The degree of reduction in water use between the two sites varied among the summer periods. The control site trees had consistently higher sap flow at corresponding values of either sapwood cross-sectional area or foliage area. Larger trees displayed smaller differences than smaller trees, between the control and the CO2 spring trees. A strong association between foliage area and sapwood cross-sectional area was found in both the control and the CO2 spring trees, the latter supporting a smaller foliage area at the corresponding sapwood stem cross-sectional area. The specific leaf area (SLA) of the foliage was not influenced by site. The results are discussed in terms of the effects of elevated CO2 on plant water use at the organ and whole-tree scale.
Keywords: Drought; Mediterranean; natural CO2 springs; Quercus ilex; sap flow; Stomatal conductance; water relations

Vulnerability of xylem to embolism in relation to plant hydraulic resistance in Quercus pubescens and Quercus ilex co-occurring in a Mediterranean coppice stand in central Italy - Tognetti, R; Longobucco, A; Raschi, A (New Phytologist, 1998)
The seasonal patterns of xylem embolism and xylem transport properties in Quercus pubescens Willd. and Quercus ilex L. trees growing in a natural mixed coppice stand in conditions of severe water stress were investigated. Xylem embolism was evaluated in both dehydrating branches and in apical twigs during a whole year. Measurements of xylem water potential were conducted from predawn to sunset on selected sunny days. On the same days, diurnal courses of leaf conductance were monitored. Measurements of half-hourly sap flow were made by the heat-pulse technique throughout the summer. At the onset of summer, a sharp decrease in water potential was observed in both species. Full recovery of water potentials was observed for both species after the first major rainfall event in September. Both experienced serious embolism throughout the year, ranging between minima of c. 60% (expressed as percentage loss of hydraulic conductivity) after the rains in autumn and after bud burst in spring, and maxima of c. 80% during summer and after freezing-thawing events during the winter season. A significant negative linear relationship was found between water potential and xylem embolism in branches dehydrating in air for Q. pubescens and Q. ilex. Q. pubescens had greater efficiency in hydraulic transport (higher specific conductivity and leaf specific conductivity) by the xylem than Q. ilex. In June, leaf conductance was high early in the morning and decreased gradually during the day. Midday depression of leaf conductance, as a result of high evaporative demand combined with water deficit, was observed in both species. In August, leaf conductance of both species was greatly reduced, as water potential dropped to extremely low values, and the stomata were almost completely closed during the afternoon. No hysteresis resulting from plant capacitance was observed in the relationship between shoot water potential and sap flow. Q. pubescens exhibited very high values of whole-tree hydraulic resistance between July and September, whereas Q. ilex generally showed lower values. The effect of soil moisture depletion on the relationship between sap flow and shoot water potential appears as a lowering of water potential at zero flow. A significant decrease of whole-tree hydraulic resistance in both species was observed with the onset of the autumn, preceding the partial recovery of twig hydraulic conductivity. The results demonstrate that both Q. pubescens and Q. ilex, although highly tolerant of severe water stress and tissue dehydration, operate at the limits of safety which are surpassed under severe droughts, and prolonged climatic stress might predispose these Quercus species to decline.
Keywords: cavitation; Drought; Hydraulic resistance; Quercus ilex L.; Quercus pubescens Willd.; water relations; xylem embolism

Vulnerability to freeze stress of seedlings of Quercus ilex L.: an ecological interpretation - Nardini, Andrea; Ghirardelli, Lia; Salleo, Sebastiano (Ann. For. Sci., 1998)
The vulnerability to freeze stress of seedlings of Quercus ilex L. was studied with the aim of defining the limits of the potential distribution area of this species in its northernmost habitat. In December 1996 seedlings were freeze stressed up to -8 °C for 3 d. Frost caused extensive functional damage to seedlings in terms of: a) leaf water status; b) root (Kr) and stem (Ks) hydraulic conductance; c) tissue disorder in the root (only nine seedlings out of 50 survived). In comparison with unstressed seedlings, Kr and Ks of freeze-stressed seedlings were reduced by 90 %. Root anatomy of freeze-stressed seedlings revealed that: a) cortex cells were dehydrated and had become separated from one another; b) the endodermis was oversuberized, thus isolating the stele from the cortex. Our conclusion was that Q. ilex is extremely vulnerable to freeze stress so that the distribution area of the species is restricted to zones with no frost events
Keywords: freeze stress; Quercus ilex L.; root and stem hydraulic conductance; water relations

Thirty years of in situ tree growth under elevated CO2: a model for future forest responses? - Hättenschwiler, S; Miglietta, F; Raschi, A; Körner, C (GLOBAL CHANGE BIOLOGY, 1997)
Rising concentrations of atmospheric carbon dioxide have been predicted to stimulate the growth of forest trees. However, long-term effects on trees growing to maturity and to canopy closure while exposed to elevated CO2 have never been examined. We compared tree ring chronologies of Mediterranean Quercus ilex which have been continuously exposed to elevated CO2 (around 650 mu mol mol(-1)) since they were seedlings, near two separate natural CO2 springs with those from trees at nearby ambient-CO2 `control' sites. Trees grown under high CO2 for 30 years (1964-93) showed a 12% greater final radial stem width than those growing at the ambient-CO2 control sites. However, this stimulation was largely due to responses when trees were young. By the time trees were 25-30 y old the annual difference in tree ring width between low and high CO2 grown trees had disappeared. At any given tree age, elevated CO2 had a relatively greater positive effect on tree ring width in years with a dry spring compared to years with more rainfall between April and May. This indicates a beneficial effect of elevated CO2 on tree water relations under drought stress. Our data suggest that the early regeneration phase of forest stands can be accelerated in CO2-enriched atmospheres and that maximum biomass per land area may be reached sooner than under lower CO2 concentrations. In our study, high CO2 grown Q. ilex trees reached the same stem basal area at the age of 26 y as control trees at 29 y,i.e. three years earlier (faster turnover of carbon?). Reliable predictions of the future development of forests need to account for the variable responses of trees over their entire lifetime. Such responses to elevated CO2 can presently only be assessed at such unique field sites.
Keywords: Basal area; Dendrochronology; forest regeneration; Mediterranean forests; natural CO2 springs; Quercus ilex; Tree ring; water relations

Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O. (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Water relations of oak species growing in the natural CO2 spring of Rapolano (central Italy) - Tognetti, R; Giovannelli, A; Longobucco, A; Miglietta, F; Raschi, A (Ann. For. Sci., 1996)
The effect of elevated atmospheric carbon dioxide on water relations was examined on downy oak (Quercus pubescens) and holm oak (Q ilex) trees. The study was conducted on trees growing in a naturally enriched CO2 spring. Sap velocity and sap flow were measured by the heat pulse technique. On the same trees, daily courses of xylem water potential, leaf conductance and transpiration were monitored. Plant water relations were evaluated by pressure-volume analysis method on shoots; on the same branches, relative conductivity of xylem was measured. Both species exhibited increased osmotic potential and decreased symplasmic fraction of water in trees adapted to increased CO2. Downy oak showed lower stomatal conductance under elevated CO2, but holm oak did not. Both species displayed higher sap flow in control trees. In both species, increased carbon dioxide did not influence xylem embolism formation.
Keywords: Drought; Elevated CO2; embolism; Quercus ilex; Quercus pubescens; sap flow; water relations

Water relations of six sclerophylls growing near Trieste (Northeastern Italy): has sclerophylly a univocal functional significance? - Nardini, Andrea; Gullo, Maria Assunta Lo; Tracanelli, Stefano (Giornale botanico italiano, 1996)
Abstract The annual time course of the water relations of six sclerophylls has been studied with the aim of: a) defining strategies adopted for withstanding summer water stress and b) to check whether their common sclerophyllous habitus could represent a case of convergent evolution devoted to a univocal functional role. In particular, Phillyrea latifolia L. showed to behave like a drought tolerant as indicated by deep summer drop in leaf water potential (?1) to near the full turgor loss point (?lp) and in leaf relative water content (RWC) as caused by xylem cavitation. Prunus laurocerasus L. and Laurus nobilis L. showed to be drought avoiding water spenders in that their ?1 dropped in summer causing prompt recovery in RWC. This was made possible by low cavitation in their twigs. Ilex aquifolium L. was a typical drought avoiding water saver in that both ?1 and RWC remained at very high levels throughout the year. Quercus ilex L. behaved like a drought avoiding water spender which switched to drought tolerance in the warmest period of the year. This was explained by its high vulnerability to cavitation. The extreme heterogeneity of the six species studied suggested that sclerophylly cannot be interpreted as an anatomical feature leading to a specific and unifying functional role, at least as regards drought resistance.
doi: 10.1080/11263509609438352
Keywords: drought tolerance (PG); sclerophylls; water relations

Water relations, gas exchange, and growth of resprouts and mature plant shoots of Arbutus unedo L. and Quercus ilex L. - Castell, Carles; Terradas, Jaume; Tenhunen, J D (Oecologia, 1994)
Resprout and mature plant shoot growth, leaf water status and gas exchange behavior, tissue nutrient content, flowering, and production were studied for co- occurring shallow-rooted (Arbutus unedo L.) and deep- rooted (Quercus ilex L.) Mediterranean tree species at the Collserola Natural Park in Northeast Spain. Resprouts showed higher growth rates than mature plant shoots. During fall, no differences in eco-physiological perfor- mance of leaves were found, but mobilization of carbo- hydrates from burls strongly stimulated growth of fall re- sprouts compared to spring resprouts, despite low expo- sed leaf area of the fall shoots. During summer drought, resprouts exhibited improved water status and carbon fixation compared to mature plant shoots. Shoot growth of Q. iIex was apparently extended due to deep rooting so that initial slower growth during spring and early summer as compared to A. unedo was compensated. Tis- sue nutrient contents varied only slightly and are postula- ted to be of minor importance in controlling rate of shoot growth, perhaps due to the relatively fertile soil of the site. Fall flowering appeared to inhibit fall shoot growth in A. unedo, but did not occur in Q. ilex. The results de- monstrate that comparative examinations utilizing vege- tation elements with differing morphological and physio- logical adaptations can be used to analyze relatively complex phenomena related to resprouting behavior. The studies provide an important multi-dimensional back- ground framework for further studies of resprouting in the European Mediterranean region.
Keywords: Growth; photosynthesis; Resprouts; Sclerophyll shrubs and trees; water relations

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O A; Oliveira, G; Martins-Loução, M a; Catarino, F M (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O. A.; Oliveira, G.; Martins-Loução, M. A.; Catarino, F. M. (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E.; Bousquet, F.; Ducrey, M. (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E; Bousquet, F; Ducrey, M (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations

Water Relations of Evergreen Sclerophylls. I. Seasonal Changes in the Water Relations of Eleven Species from the Same Environment - RHIZOPOULOU, S; MITRAKOS, K (Annals of Botany, 1990)
Leaf water relationships were studied in eleven evergreen sclerophyll species from a macchia near Athens, Greece. Water (ψ), solute (ψs) and turgor (ψp) potentials as well as relative water content (RWC) and stomatal conductance were measured during the course of a year. Relatively high values of water potential were measured initially in the young expanding leaves during the 60–90 d of the growth period. After this period a soil moisture deficit developed and leaves increased to full size. During the drought period leaf water potential and solute potential values, as well as stomatal conductance were low. The results show that during the dry season (Jun.–Aug.) all species are at or near zero turgor and this occurs in Arbutus, Myrtus and Nerium at around −1.5 MPa, in Ceratonia, Pistacia and Quercus at around −2.0 MPa, in Laurus, Olea and Phillyrea below −3·5 MPa. These values largely reflect differences in ψs at this time. Also, the seasonal variations in the water relations components reflect the responses of the different species to variation in water availability.
Keywords: Arbutus andrachne L.; Arbutus unedo L.; Ceratonia siliqua L.; Laurus nobilis L.; Mediterranean Region; Myrtus communis L.; Nerium oleander L.; Olea europaea L.; Phillyrea Iatifolia L.; Pistacia lentiscus L.; Quercus coccifera L.; Quercus ilex L.; Stomatal conductance; water relations